A bosonic realisation of the 1-D parabose oscillator - Cova, Ramón (Ciencia)
In the Fock space of two Bose operators all the representations of the 1-D Parabose oscillator are realised. States of (p+2n-1) bosons are shown to stand for states of n parabosons of order p.